Degradation of the Tri Hita Karana Implication in Three-Star Hotels Landscape in Bali: Implications for Cultural and Architectural Sustainability - I Nyoman Miyoga; I Wayan Suka Yasa; I Wayan Muka (International Journal of Interreligious and Intercultural Studies, 2025)
This study examines the degradation of Tri Hita Karana (THK) implementation in tourism landscapes, particularly in the gardens of three-star hotels in Kuta sub-district, Badung Regency, Bali, influenced by modernization, capitalization, and globalization. THK, as a philosophy of Balinese life, emphasizes the balance of human relationships with God (parahyangan), with fellow humans (pawongan), and with the environment (palemahan). However, this research found that economic and political pressures have led to significant shifts in the implication of THK values in hotel landscape design, where traditional elements are often neglected in favor of spatial efficiency, modern aesthetics, and economic factors aimed at maximizing profit. This study employs a qualitative approach using a case study method. Data were collected through observations, in-depth interviews, and document analysis, and were analyzed using critical theories such as Foucault’s power-knowledge relations theory, which highlights the interconnection between power and knowledge; Giddens’ structuration theory, which explains the duality between agents (human resources) and social structures in relation to time and space; and Derrida’s deconstruction theory, which reveals hidden dual meanings. The findings reveal how agents such as architects, developers, and the government contribute to the degradation of THK values. The study highlights the discrepancy between regulations and actual implementation. Additionally, there is evidence of THK knowledge manipulation by capital owners to legitimize deviations from cultural values. This research makes a theoretical contribution by strengthening and expanding the understanding of THK application in modern architecture. Moreover, it offers practical recommendations to enhance the preservation of Balinese culture through regulatory reinforcement, education, and collaboration between the government, the private sector, and the community